Chinches auxiliares del algodón en Andalucía occidental - Durán, J. M.=700 1 Alvarado, M.; Serrano, A.; De La Rosa, A.; Ortíz, E.
Resumenes (Es, En)
15 fotos; 41 ref.
Keywords: DERAEOCORIS; GEOCORIS; NABIS; ORIUS; DINAMICA DE LA POBLACION; CHINCHES AUXILIARES